Differences in competition statistics between winners and losers in male and female tennis players in Olympic Games - Fernández-Garcia, Á. I.; Blanca-Torres, J. C.; Nikolaidis, P.T.; Torres-Luque, G. (German Journal of Exercise and Sport Research, 2019)
The aim of this study was to examine differences in the performance indicators between winners and losers in male and female high-level tennis players. A total of 128 tennis singles matches played on grass court surface at the London 2012 Olympic Games were analyzed. Data were collected from the official website of the Olympics and the following groups of variables were analyzed: serve variables (n = 7), serve return variables (n = 3) and game-related variables (n = 5). The results showed that winners had greater (p < 0.05) values of second serve (%), aces, first and second serve points won (%), points won on first and second serve return (%), break points played and break points won (%). Furthermore, they get more winners with both groundstrokes and net points won (%) than losers in both sexes. Losers also committed more doubles faults than winners, and in the male category more unforced errors, whereas female winners get higher serve maximum speed (p < 0.05). Performance indicators according to the result of the match predicted that break points won, first serve points won (%) and first serve return points won (%) are the most relevant variables in males (SC = 0.434; SC = 0.340; SC = 0.327), whereas it was the break points won (SC = -0.372) in females. Therefore, coaches should consider the variation of the competition statistics by gender if they want to enhance the chances of success of their players. In der vorliegenden Studie sollten Unterschiede in Leistungsindikatoren zwischen Siegern und Verlierern im Weltklassetennis der Männer und Frauen untersucht werden. Insgesamt 128 Spiele im Tenniseinzel auf Rasen bei den Olympischen Spielen von London 2012 wurden betrachtet. Die Daten stammten von der offiziellen Website der Olympischen Spiele. Folgende Variablengruppen wurden analysiert: Aufschlagvariablen (n = 7), Return-Variablen (n = 3) und spielbezogene Variablen (n = 5). Die Auswertung ergab, dass Sieger höhere Werte (p < 0,05) in Bezug auf den zweiten Aufschlag (%), Asse, bei erstem und zweitem Aufschlag gewonnene Punkte (%), bei Return des ersten und zweiten Aufschlags gewonnene Punkte (%), gespielte Breakbälle und gewonnene Breakbälle (%) aufwiesen. Weiterhin erzielten sie unabhängig vom Geschlecht mehr Punkte mit Grundschlägen ("groundstrokes") und am Netz (%) als Verlierer. Verlierern unterliefen mehr Doppelfehler als Siegern und bei Männern mehr unerzwungene Fehler, während Siegerinnen beim Aufschlag eine höhere Maximalgeschwindigkeit erreichen (p < 0,05). Leistungsindikatoren gemäß dem Matchergebnis sagten voraus, dass gewonnene Breakbälle, bei erstem Aufschlag gewonnene Punkte (%) und bei Return des ersten Aufschlags gewonnene Punkte (%) die wichtigsten Variablen bei Männern sind (SC = 0,434; SC = 0,340; SC = 0,327), während es bei Frauen die gewonnenen Breakbälle waren (SC = 0,372). Daher sollten Trainer geschlechtsbezogene Unterschiede in den Wettkampfstatistiken berücksichtigen, wenn sie die Erfolgsaussichten ihrer Spieler erhöhen wollen.